Development of creative anti-smoking online PSA - Ooi, Lai Tat (Open University Malaysia, 2018)
Advertising is an audio or visual form of marketing communication that employs an openly sponsored, non-personal message to promote or sell a product, service or idea (Stanton, 1984). Sponsors of advertising are often businesses who wish to promote their products or services. Advertising is differentiated from public relations in that an advertiser usually pays for and has control over the message. It is differentiated from personal selling in that the message is non-personal, as in: not directed to a particular individual. Advertising is communicated through various mass media (Bovee & Arens, 1992), including old media such as newspapers, magazines, television, radio, outdoor advertising or direct mail; or new media such as search engine results, social media, websites or text messages. The actual presentation of the message in a medium is referred to as an advertisement or "ad".